(-b/3)=6

Simple and best practice solution for (-b/3)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-b/3)=6 equation:


b in (-oo:+oo)

-b/3 = 6 // - 6

-b/3-6 = 0

-1/3*b-6 = 0 // + 6

-1/3*b = 6 // : -1/3

b = 6/(-1/3)

b = -18

b = -18

See similar equations:

| 5-(f+3)=5f | | 91=-4(6-6b)-5 | | 2ln(x)=ln(21) | | 17=32 | | 40=16t^2+88t | | 20=(1/4c) | | 75=3x^2-9 | | 18x+5=20x+1 | | log*(x+11)-log(2)=log*(5x+1) | | 21=-7u | | 18+5=20+1 | | 2/3x-16 | | (x/4)=3 | | 3y=8-7y-1 | | (12b-6)-(7-18b)= | | (2n^2+4n+3)(2n-3)= | | (-7x)(-1/7) | | 76.9-34.782= | | 8x+3.5=36 | | 6-10=1 | | 16x^2+7x-9=0 | | 3(1+2y)-5=6y-2 | | .468*4.8= | | -14.49-3.9d=3.3(d+3.9) | | 5=3n-n+5 | | 576*.6= | | -2x^2+20x=-82 | | a^2-4a-24+6a= | | 3(1-2y)-5=6y-2 | | 2a-10=44+8a | | -2d+18-4b=60 | | 9x+2+5x+4= |

Equations solver categories